Leadership in Action: Quality Control: Why Leaders Need to Understand Personality - Hogan, Robert; Kaiser, Robert (Center for Creative Leadership, 2008)
With a clear understanding of how people are alike and the important ways in which they differ, managers are in a strong position to be effective leaders.